2015
DOI: 10.1016/j.jvs.2015.04.454
|View full text |Cite
|
Sign up to set email alerts
|

Management of late main-body aortic endograft component uncoupling and type IIIa endoleak encountered with the Endologix Powerlink and AFX platforms

Abstract: Although a small number of secondary interventions were needed after EVAR with the Endologix Powerlink or AFX endografts, most were undertaken for late main-body component uncoupling and type IIIa endoleak, which can occur after sideways displacement of the endograft in large and angulated AAAs. Patients treated before 2013 under the old instructions for use should be evaluated for signs of impending component separation and monitored annually, noting that expected indicators of endograft failure, such as incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 24 publications
0
27
0
1
Order By: Relevance
“…Since the beginning of 2013 revised IFU, requirement of a minimum component overlap of at least 30 mm to 40 mm have been introduced, and these were carefully followed in the present study. Similarly, in the Skibba et al [6] series, no new type III endoleaks have been observed in patients treated with the revised IFU. Meticulous preoperative planning and proper selection of endograft components for a sufficient overlap are of utmost importance for endograft uncoupling and type III endoleak prevention.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…Since the beginning of 2013 revised IFU, requirement of a minimum component overlap of at least 30 mm to 40 mm have been introduced, and these were carefully followed in the present study. Similarly, in the Skibba et al [6] series, no new type III endoleaks have been observed in patients treated with the revised IFU. Meticulous preoperative planning and proper selection of endograft components for a sufficient overlap are of utmost importance for endograft uncoupling and type III endoleak prevention.…”
Section: Discussionmentioning
confidence: 66%
“…From investigating 701 EVAR patients treated with the Endologix Powerlink or AFX endograft, Skibba et al [6] recently reported a type IIIa endoleak in 17 patients (2.4%). Welborn et al [7] reported a similar incidence (2.3%) in 108 patients treated with the AFX system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7,8 However, the incidence of those experiencing modular migration without endoleak remained unclear. 9 Additionally, the true incidence of clinically significant type IIIa endoleaks may be much higher. In 2016, our group published a 7.2% modular separation event rate associated with implantation of the AFX aortic graft which led to the voluntary withdrawal of a portion of available grafts by Endologix.…”
Section: Discussionmentioning
confidence: 99%
“…Fortunately, with newer generation devices, separation occurs less frequently. 31 Endograft limb kinking can occur in the setting of inferior translocation, with potential for graft occlusion or thrombosis. 32 Graft occlusions typically occur within the first year of placement, with posited risk factors for limb occlusion including small aortic bifurcations and tortuous, angulated iliac arteries 33,34 (►Fig.…”
Section: Structural Complicationsmentioning
confidence: 99%